2020
DOI: 10.20944/preprints202001.0285.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Oxidative Stress Toxicity and Lowered Antioxidant Defenses in Temporal Lobe Epilepsy and Mesial Temporal Sclerosis: Associations with Psychiatric Comorbidities

Abstract: Oxidative stress toxicity (OSTOX), as well as lowered antioxidant defenses (ANTIOX), play a role in temporal lobe epilepsy (TLE). Nevertheless, the associations between OSTOX/ANTIOX and psychiatric comorbidities in TLE are largely unknown.Thus, this study examines plasma malondialdehyde (MDA), lipid hydroperoxides (LOOH), advanced oxidation protein products (AOPP), nitric oxide metabolites (NOx), total radical trapping antioxidant parameter (TRAP) and sulfhydryl (-SH) groups in Depression due to TLE (n=25); An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In addition, those authors reported that the ratio of total peroxides versus antioxidants potential was significantly higher in patients with deficit schizophrenia. Nevertheless, our results show that deficit schizophrenia is accompanied by increased oxidative stress toxicity, which attributable to increased AOPP levels [63,64] and that mesial temporal sclerosis is accompanied by highly increased MDA levels, whereas AOPP levels are less severely disordered [62]. Therefore, it appears that increased protein oxidation without severe lipid peroxidation and aldehyde formation is a more specific OS biomarker profile of deficit schizophrenia.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, those authors reported that the ratio of total peroxides versus antioxidants potential was significantly higher in patients with deficit schizophrenia. Nevertheless, our results show that deficit schizophrenia is accompanied by increased oxidative stress toxicity, which attributable to increased AOPP levels [63,64] and that mesial temporal sclerosis is accompanied by highly increased MDA levels, whereas AOPP levels are less severely disordered [62]. Therefore, it appears that increased protein oxidation without severe lipid peroxidation and aldehyde formation is a more specific OS biomarker profile of deficit schizophrenia.…”
Section: Discussionmentioning
confidence: 59%
“…It has been shown that ALDH3B1 plays a critical role in the cellular defense against oxidative stress processes and aldehyde toxicity [ 112 , 113 ]. Oxidative stress toxicity and lowered antioxidant defense are considered as contributing factors in the genesis and progression of epilepsy [ 114 116 ], while epileptic seizures, especially recurrent seizures may also increase oxidative stress, which will result in treatment resistance [ 117 120 ]. Oxidative stress can lead to the occurrence of lipid peroxidation (LPO) and resulting in plenty of aldehydes, such as 4-hydroxy-2-nonenal (4HNE) [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Immune activation is frequently associated with activation of oxidative and nitrosative stress (O&NS) pathways and with lowered levels of key antioxidants such as high-density lipoprotein cholesterol (HDL-c) and vitamins including vitamin D. 24,25 There is now evidence that both O&NS and lowered antioxidant levels play a key role in the pathophysiology of affective disorders and schizophrenia. 26,27 In those disorders, increased nitro-oxidative stress in indicated by elevated levels of lipid hydroperoxides (LOOH) and malondialdehyde (both indicating lipid peroxidation), advanced oxidation protein products (indicating increased oxidation of proteins) and nitric oxide (NO) metabolites (NOx). 27,28 Moreover, both disorders are accompanied by lowered levels of key antioxidants including HDL-c, vitamin D, and albumin.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 In those disorders, increased nitro-oxidative stress in indicated by elevated levels of lipid hydroperoxides (LOOH) and malondialdehyde (both indicating lipid peroxidation), advanced oxidation protein products (indicating increased oxidation of proteins) and nitric oxide (NO) metabolites (NOx). 27,28 Moreover, both disorders are accompanied by lowered levels of key antioxidants including HDL-c, vitamin D, and albumin. 29 The neurotoxicity theories of mood disorders and schizophrenia consider that the neurotoxic effects of immune and O&NS (IO&NS) pathways cause dysfunctions in gray and white matter functional plasticity (including axon sprouting, synaptogenesis, glial changes, neurogenesis, and myelin formation) thereby explaining the onset of affective disorders and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation